Association of genetic variations in neurokinin‐2 receptor with enhanced cough sensitivity to capsaicin in chronic cough - Park, H‐K (BMJ Group, 2006)
BACKGROUND: Chronic cough is associated with increased sensitivity to inhaled capsaicin, and both tachykinins and their receptors play important roles in the cough reflex. However, associations between polymorphisms of the tachykinin receptor genes and cough sensitivity in patients with non‐productive chronic cough have not been reported. METHODS: Direct sequencing was used to identify single nucleotide polymorphisms (SNPs) in the genes for the neurokinin‐1 and neurokinin‐2 receptors (NK‐1R and NK‐2R, respectively). Informative non‐synonymous SNPs were scored using the single base extension method for 312 patients with chronic cough and for 100 age matched healthy controls. The cough response to capsaicin was recorded for 312 patients with chronic cough, and the potential genetic association between cough sensitivity to capsaicin and the NK‐1R and NK‐2R genotypes was evaluated. RESULTS: Two informative SNPs were identified in NK‐2R (Gly231Glu and Arg375His), whereas no informative SNP was found in NK‐1R. After adjusting for atopy, sex, age, and smoking, the prevalence of enhanced cough sensitivity to capsaicin was higher in the chronic cough patients with the 231Glu allele (p = 0.004; OR 1.69 (95% CI 1.18 to 2.42)) and the 231Glu_375Arg haplotype (p = 0.003; OR 1.71 (95% CI 1.20 to 2.24)]. Moreover, the lowest capsaicin concentration to cause five consecutive coughs (C5) was significantly lower in patients with 231Glu (mean (SD) 44.1 (53.2) v 60.9 (55.8) μM/l, p = 0.04) and those with 231Glu_375Arg (43.2 (52.7) v 69.6 (52.0) μM/l, p = 0.03). CONCLUSIONS: The results of this study suggest that NK‐2R gene polymorphisms are involved in the enhanced cough sensitivity to capsaicin of patients with chronic cough.